2013
DOI: 10.1007/s12928-013-0217-5
|View full text |Cite
|
Sign up to set email alerts
|

Laser in infra-popliteal and popliteal stenosis (LIPS): retrospective review of laser-assisted balloon angioplasty versus balloon angioplasty alone for below knee peripheral arterial disease

Abstract: Despite the use of laser technology over the last decade, there are limited data to show its procedural and clinical success in infra-popliteal disease. We hypothesized that laser-assisted balloon angioplasty (LABA) is at least similar or better in procedural and peri-procedural outcomes compared to balloon angioplasty (BA) alone, despite adverse lesion characteristics prior to intervention. Retrospective chart and angiogram review of consecutive critical limb ischemia (CLI) patients who underwent endovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…The end score is added up from four categories. Patient could have a minimum score of 0 to max score of 12 (Supporting Information Table 5) .…”
Section: Resultsmentioning
confidence: 99%
“…The end score is added up from four categories. Patient could have a minimum score of 0 to max score of 12 (Supporting Information Table 5) .…”
Section: Resultsmentioning
confidence: 99%
“…While LABA was associated with better procedural angiographic success and improving lesion severity score, despite having worse baseline angiographic characteristics (more chronic total occlusion and TASC C/D lesions) as reported before [5], this was associated with similar rate of major ipsilateral limb amputations, any ipsilateral (major and/or minor) amputations and repeat revascularizations compared with BA at median follow up time of 36 months. Periprocedural complication rates were similar, except for less distal embolization in LABA.…”
Section: Discussionmentioning
confidence: 61%
“…Despite having more TASC-D lesions in LABA group (92.4 vs. 66.5%, P < 0.0001), the rate of angiographic success (residual stenosis <50%, 97.7 vs. 89.2%, P < 0.001) were higher in LABA compared to BA. Complication rates during index procedure were similar except for lower incidence of distal embolization in LABA group (0.5 vs. 3.3%, P = 0.004) [5]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in 2013 the Laser in infra-popliteal and popliteal stenosis (LIPS) retrospective review, analyzed LA vs PTA for IPOD. The study showed that LA plus PTA had a 5 times greater likelihood of improvement in the IPA lesion severity score compared to PTA alone [ 41 ].…”
Section: Introductionmentioning
confidence: 99%